Respuestas

2012-04-25T22:16:28+02:00

m(-a +6n-4) + m( 6-a-5n) + m(-2-5n+3a)=0

m.-a +6n -4+ 6-a-5n -2-5n+3a=0

m. +6n-5n-5n-a-a+3a=-4+6-2

m.-4n +5a=0

m=4n-5a

a=4n+5m

 

                                                              

2012-04-25T22:43:07+02:00

buenas tardes.solucion:-am+6mn+6

                                   -am-5mn -4
                                   3am-5mn-2
                               ----------------------
                                   am-4mn   0

la solucion correcta es la opcion a)am-4mn          saludos.